Neurospora tetrasperma bibliography - David D. Perkins (Fungal Genetics Reports, 1994)
Dodge's discoveries of pseudohomothallism and of heterokaryosis were both accomplished using Neurospora tetrasperma, which remained his favorite species. In the decades following Dodge's work, studies involving N. tetrasperma were continued in only a few laboratories, notably those of Alfred Sussman, Branch Howe, Adrian Srb, and Robert Metzenberg. The species has now begun to receive increased attention, both for comparative molecular-evolutionary studies and for studies that take advantage of certain unique features. Nuclear, mitochondrial, and plasmid DNA's have been used to explore phylogenetic relationships. Work is progressing on ascus development, recombination, vegetative incompatibility, and mating type. The following list is a first attempt to bring together the scattered literature on N. tetrasperma. (A few entries are also included that deal with pseudohomothallism generally.) The search has not been exhaustive. Please call any nontrivial omissions to my attention.